2021
DOI: 10.1038/s41541-021-00291-x
|View full text |Cite
|
Sign up to set email alerts
|

ChAdOx1-vectored Lassa fever vaccine elicits a robust cellular and humoral immune response and protects guinea pigs against lethal Lassa virus challenge

Abstract: Lassa virus (LASV) infects hundreds of thousands of individuals each year, highlighting the need for the accelerated development of preventive, diagnostic, and therapeutic interventions. To date, no vaccine has been licensed for LASV. ChAdOx1-Lassa-GPC is a chimpanzee adenovirus-vectored vaccine encoding the Josiah strain LASV glycoprotein precursor (GPC) gene. In the following study, we show that ChAdOx1-Lassa-GPC is immunogenic, inducing robust T-cell and antibody responses in mice. Furthermore, a single dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 77 publications
1
36
0
1
Order By: Relevance
“…ChAdOx1 is a chimpanzee adenovirus vector platform that has been employed in the development of vaccine candidates for several pathogens. A single dose of ChAdOx1-vectored vaccine fully protects against Rift Valley fever virus, Middle East respiratory syndrome coronavirus, Lassa virus, or Zika virus in animal models of infection ( 35 , 48 51 ). In the same vein, we also observed the efficacy of a single dose of the recombinant ChAdOx1 as IFNAR(-/-) mice immunized with a single dose of ChAdOx1-NS1-NS2-Nt were fully protected against BTV-4M, showing an aviremic status throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…ChAdOx1 is a chimpanzee adenovirus vector platform that has been employed in the development of vaccine candidates for several pathogens. A single dose of ChAdOx1-vectored vaccine fully protects against Rift Valley fever virus, Middle East respiratory syndrome coronavirus, Lassa virus, or Zika virus in animal models of infection ( 35 , 48 51 ). In the same vein, we also observed the efficacy of a single dose of the recombinant ChAdOx1 as IFNAR(-/-) mice immunized with a single dose of ChAdOx1-NS1-NS2-Nt were fully protected against BTV-4M, showing an aviremic status throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of NAbs as a protective endpoint for LASV vaccines has only recently been made clear through the success of several passive immunization studies with monoclonal bNAbs in animal models (Cross et al, 2016(Cross et al, , 2019Mire et al, 2017). Yet, various studies have also shown protection to LASV challenge in the absence of measurable (pseudovirus) NAb responses, suggesting a role for cellular immunity or non-neutralizing Ab effector functions in vaccine-induced protection (Abreu-Mota et al, 2018;Fischer et al, 2021;Mateo et al, 2021). Our guinea pig study provides additional evidence that NAb responses may not be the sole determinant for protection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a single vaccinated dose of the ChAdOx1 vector-based vaccine expressing the Josiah LASV GPC has been shown to induce robust T-cell and antibody responses in mice and can protect guinea pigs against morbidity and mortality following lethal challenge of the vaccinated animal with a guinea pig-adapted Josiah LASV strain. A prime-and-boost vaccination of this vaccine has also been shown to significantly enhance LASV antigen-specific antibody titers and clear LASV from the tissues of the virus-challenged animals [ 177 ]. Therefore, adenovirus vectored LASV vaccines have shown some encouraging results in guinea pig models that warrant additional testing in the gold-standard non-human primate LF model.…”
Section: Lf Therapeuticsmentioning
confidence: 99%